1999
DOI: 10.1016/s0886-3350(99)80047-9
|View full text |Cite
|
Sign up to set email alerts
|

Fitting contact lenses after myopic keratomileusis

Abstract: After lamellar refractive surgery, the topography of the cornea is significantly altered. Although the postoperative keratometry readings are steeper than the actual curvature, they are reasonably reliable for determining the base curve of the initial trial lens, validating the use of conventional methods of fitting rigid contact lenses in patients who have had MKM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A large range exists in the literature, from fitting 0.1 mm to more than 0.4 mm (0.50 D to more than 2 D) steeper than the flat or mean postoperative keratometry value. 4,[15][16][17][18] Only two studies have used CVK maps to guide in the selection of base curves after b Significant and high correlation between gas-permeable lens base curve and corneal curvature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large range exists in the literature, from fitting 0.1 mm to more than 0.4 mm (0.50 D to more than 2 D) steeper than the flat or mean postoperative keratometry value. 4,[15][16][17][18] Only two studies have used CVK maps to guide in the selection of base curves after b Significant and high correlation between gas-permeable lens base curve and corneal curvature.…”
Section: Discussionmentioning
confidence: 99%
“…In the traditional method of diagnostic trial lens application, simulated keratometry was used as a starting point for lens base curve selection. The formula used was based on findings from a study by Chou et al, 17 who fitted a series of patients after myopic keratomileusis with GP lenses on average 1.3 diopters (D) steeper than the mean postoperative flat keratometric reading. Once the diagnostic lens was applied, the fit was titrated to achieve central clearance, alignment in the mid periphery, and a peripheral band of 2 to 3 mm of adequate axial edge lift to provide even corneal clearance but not enough to break the tear meniscus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, no adverse physiological problems such as oedema were identified with contact lens wear in this study. As with PRK, most authors advocate the use of rigid gas permeable lenses in post‐LASIK eyes (Szczotka and Aronsky, 1998; Chou et al , 1999; Bufidis et al , 2000; Ward, 2001).…”
Section: Wearing Time and Follow‐upmentioning
confidence: 99%
“…Excessive central pooling, poor stability and centration may occur with conventional rigid gas permeable (CRGP) lenses because the corneal topography is typically flatter centrally. Some studies have, however, reported success with the use of CRGP and soft contact lenses after refractive surgery (Shipper et al , 1995; Astin et al , 1996; Lee and Kastl, 1998; Chou et al , 1999; Lim et al , 1999; Ward, 2001). When a larger refractive error is attempted (>−7 dioptres), the ablated zone may be wider and deeper, which makes lens fitting even more challenging (Astin et al , 1996; Chou et al , 1999; Astin, 2000).…”
Section: Introductionmentioning
confidence: 99%